Comparison of The Financial Performance of Banking Companies Before and After Merger or Acquisition - Zahara, Zahara; Alang Sari, Putrie; Ramadhea Jr, Syafira; Andriani, Wiwik (Publication Division of International Ecsis Association, 2023)
In competitive era nowadays, management is expected to make the right business strategies, including merger or acquisition actions, for optimizing the value of the company. This study aims to analyze the differences in financial performance before and after a merger or acquisition. The research method used is a quantitative approach with secondary data obtained from the idx.co.id website. The population in this study were banking sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique was carried out using purposive sampling method with a total sample of 6 companies. The research data used are financial statements for 2 years before and 2 years after the merger and acquisition. The data is processed using the SPSS v.25 application. The results of the study using the Wilcoxon signed test showed that there were significant differences in TATO and EPS after the merger or acquisition, then there were no significant differences in CR, DER, ROA, and NPL.